Edukasi Cuci Tangan dan Pembagian Masker bagi Ibu Hamil - Afrida, Bq. Ricca; Aryani, Ni Putu; Annisa, Nurul Hikmah; Idyawati, Susilia (Jurnal LENTERA, 2021)
Maternal mortality in Indonesia remains a big challenge. Currently, maternal health services cannot be separated from the impact both in terms of access and quality due to the outbreak of the coronavirus disease 2019 (COVID-19). The World Health Organization stated that strict health care during a pandemic will have an impact on the use of health services, especially reproductive health services. The form of this activity is education on hand washing and distribution of masks for pregnant women. The expected output from this activity is the publication of an accredited institutional journal or journal. In addition, the results of this activity will be presented and published in a community service seminar. These activities include hand washing education, hand washing practices, provision of facilities for washing hands, distribution of masks and education on how to use masks correctly. Outreach and demonstrations have been proven effective in increasing knowledge and skills about washing hands and using masks as an effort to prevent transmission of COVID-19